Relationship Between Role Family and Independence of The Elderly in Daily in The Health Center - Suarnianti, Suarnianti; Aisyah, Reski Nur; Annisa, Nurul Rezki (Jurnal Keperawatan Priority, 2025)
The elderly are an age group that is vulnerable to a decline in physical and mental abilities, so they need help with daily activities. The role of the family is important in helping the elderly stay healthy. The aim of this research is to determine the relationship between the role of the family and the independence of the elderly in fulfilling daily activities (ADL) in the UPT BLUD Bajoe Health Center, Bone Regency. The design of this study was quantitative research with a Cross Sectional, the method of taking samples using Purposive Sampling and Cluster Sampling, as many 147 respondents, collected through questionnaires. The results of the research show that there is a relationship between the role of the family and the independence of the elderly in fulfilling daily activities (ADL), with a result of ρ=0.004, then Ha is accepted. The conclusions and suggestions in this research show that there is a relationship between the role of the family and the independence of the elderly in fulfilling daily activities (ADL) in the Working Area of UPT BLUD Bajoe Health Center, Bone Regency. It is hoped that this research can provide information for health workers and families to pay more attention to the elderly in fulfilling their daily activities.